ANALYSIS OF ACCOUNTING TREATMENT OF FIXED ASSETS IN THE FORESTRY SERVICE OF JAMBI PROVINCE - Zazatia, Zazatia; Sam, Iskandar; Friyani, Rita (Jurnal Cakrawala Akuntansi, 2025)
This thesis research discusses the Analysis of Fixed Asset Accounting Treatment at the Jambi Provincial Forestry Service. The main objective of this study is to evaluate whether the accounting treatment of fixed assets at the Jambi Provincial Forestry Service complies with the Government Accounting Standards Statement (PSAP) No. 07. The research was conducted using a qualitative descriptive approach, which involved collecting data through document review, observation, and interviews with relevant officials at the Forestry Service. The analysis focused on four key aspects of fixed asset accounting: recognition, measurement, depreciation, and disclosure. The findings indicate that the Jambi Provincial Forestry Service has generally applied PSAP No. 07 correctly. Fixed assets are recognized in line with ownership criteria, measured based on acquisition cost, depreciated systematically, and disclosed appropriately in financial reports. These results show that the accounting treatment of fixed assets at the Forestry Service is consistent with the requirements of PSAP No. 07. Thus, this study contributes by providing evidence that a regional government institution has implemented PSAP No. 07 properly, reinforcing the importance of compliance with government accounting standards to ensure transparency and accountability in public sector financial reporting. Keywords: Fixed Assets, Recognition, Measurement, Depreciation, Disclosure.